Multisession transcranial direct current stimulation and memory-associated cognitive functions in healthy young adults - Kukuła, Daria; Wiłkość-Dębczyńska, Monika; Rasmus, Anna (Frontiers in Human Neuroscience, 2025)
Research suggests that cognitive ability is an important predictor of life outcomes, health, and mortality. Cognitive functions develop at different rates depending on age, and human development involves individual and multidirectional changes, which are plastic processes that last throughout life. Memory, a complex and multidimensional cognitive area, comprises various systems that work together to encode, store, and retrieve information. Working memory plays a key role in processing the information required for a current activity. In recent years, non-invasive brain stimulation techniques such as tDCS have attracted growing attention from researchers. tDCS modulates cortical activity via low-intensity current, inducing neuronal membrane polarization. This study aimed to assess the effect of tDCS on memory function in healthy individuals in early adulthood. The sample consisted of 90 volunteers aged 20–35 years which were divided into three groups: experimental, active control, and passive control. Cognitive functions were assessed using the Digit Span Test from the WAIS-R(PL), Berg’s Card Sorting Test (BCST), and the Tower of London Test (TOL). The results indicated that tDCS contributed to improvements in working memory, particularly in the auditory-verbal memory span, the effectiveness of maintaining an intended plan in memory, and the ability to remember and coordinate different components of the task. No significant changes were observed in the digit span backward measurement. This study has limitations, including the absence of long-term follow-up and lack of physiological measures such as qEEG. Nonetheless, the findings suggest that tDCS may be a promising method for enhancing memory-related cognitive functions in early adulthood.